1993
DOI: 10.1002/bjs.1800800407
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative blood transfusion and outcome after resection for colorectal carcinoma

Abstract: The degree of immunomodulation by perioperative blood transfusion and its effect on oncological surgery remain controversial. A major problem with previous clinical studies has been the inadequate patient population in each and the presence of confounding variables. To resolve some of the controversy, all studies published between 1982 and 1990 were reviewed using the statistical method of Mantel-Haentszel-Peto to determine a cumulative estimate of the direction and magnitude of this association. Some 20 paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
7

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(67 citation statements)
references
References 44 publications
0
60
0
7
Order By: Relevance
“…Chung et al, 62 Vamvakas, 17 and Brand and Houbiers 18 used meta-analysis to integrate the findings from the univariate (ie, unadjusted; Table 1) analyses of the observational studies of the association of perioperative allogeneic blood transfusion with cancer recurrence, death due to cancer recurrence, or overall mortality. The most recent meta-analysis 18 also included studies not published in English and considered 7 cancer sites; 100 observational studies were identified as eligible for analysis.…”
Section: Cancer Recurrencementioning
confidence: 99%
“…Chung et al, 62 Vamvakas, 17 and Brand and Houbiers 18 used meta-analysis to integrate the findings from the univariate (ie, unadjusted; Table 1) analyses of the observational studies of the association of perioperative allogeneic blood transfusion with cancer recurrence, death due to cancer recurrence, or overall mortality. The most recent meta-analysis 18 also included studies not published in English and considered 7 cancer sites; 100 observational studies were identified as eligible for analysis.…”
Section: Cancer Recurrencementioning
confidence: 99%
“…The first report was introduced by Gantt in 1981, who carried out the detrimental effects on cancer patients with blood transfusion (Gantt, 1981). Later some studies have also shown an deleterious effect of ABT (Chung et al, 1993;Vamvakas, 1995;Amato et al, 2006), whereas others did not (Weiden et al, 1987;Voogt et al, 1987 ;Busch et al, 1994). The conclusions of the clinical outcomes are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Allogeneic blood transfusion was one of the factors on prognosis of colorectal cancer (CRC) in many possible factors (van der Voort van Zijp et al, 2008). It has been reported that allogeneic blood transfusion may potentially increase postoperative tumor recurrence and mortality (Chung et al, 1993;Vamvakas, 1995;Amato et al, 2006). Conversely, other reports have failed to confirm a significant transfusion dependent effect (Weiden et al, 1987;Voogt et al, 1987;Busch et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A dose-dependent adverse effect of intraoperative blood transfusion on a variety of outcomes in thoracic surgical patients has been demonstrated [112]. Immunomodulation may be harmful in oncological surgery: an unfavorable impact on clinical outcomes has been demonstrated [113][114][115]. A meta-analysis of 5,915 lung cancer resection patients has demonstrated a negative association between transfusion and overall and disease-free survival [116].…”
Section: Fluid Choicementioning
confidence: 99%